Research on the Stability of the Grade Structure of a University Title - Dongping Xuan; Zhe Zhang; Wenyuan Sun (International Journal of Engineering and Management Research, 2019)
The evaluation of college teachers' title is an extremely important task in personnel management, and it is also the focus of college teachers and other professional and technical personnel. The work is policy-oriented and involves a wide range of issues. Whether it is scientific, fair and reasonable is related to whether it can mobilize the enthusiasm and creativity of teachers. It is related to the construction of the teaching staff and the adjustment of the academic echelon, which is of great significance for promoting the sustainable development of higher education.